2001
DOI: 10.1248/bpb.24.1202
|View full text |Cite
|
Sign up to set email alerts
|

DPPH (1,1-Diphenyl-2-Picrylhydrazyl) Radical Scavenging Activity of Flavonoids Obtained from Some Medicinal Plants.

Abstract: Flavonoids are a group of polyphenolic compounds, which have the diphenylpropane (C 6 -C 3 -C 6 ) skeleton, ubiquitously found in fruits and vegetables. The flavonoid family includes flavones, flavonols, flavanones, flavanonols, flavans, flavanols, leucoanthocyanidins, anthocyanidins, aurones, chalcones, and isofavones. The structural difference in each flavonoid family results from the variation in the number and arrangement of the hydroxyl groups and the extent of glycosylation of these groups. 1)Epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(164 citation statements)
references
References 16 publications
13
143
1
7
Order By: Relevance
“…However, formation of free radical intermediates from oxidized compounds, which could become important propagators of free radical chain reactions, cannot be detected by this assay (Okawa et al, 2001). The chemiluminescence method, the other experimental model used, is based on the antioxidantdependent quenching of the chemiluminescence generated by luminol/peroxidase/H 2 O 2 (Dodeigene et al, 2000).…”
Section: Antimicrobial and Antioxidant Activitiesmentioning
confidence: 99%
“…However, formation of free radical intermediates from oxidized compounds, which could become important propagators of free radical chain reactions, cannot be detected by this assay (Okawa et al, 2001). The chemiluminescence method, the other experimental model used, is based on the antioxidantdependent quenching of the chemiluminescence generated by luminol/peroxidase/H 2 O 2 (Dodeigene et al, 2000).…”
Section: Antimicrobial and Antioxidant Activitiesmentioning
confidence: 99%
“…Polyphenols are the most active antioxidant derivatives in plants. 20 Total phenolics and flavonoids content results obtained in the present study revealed that the level of these compounds in the extracts were considerable. Therefore extracts with good amount of phenolic compounds but weaker scavenging activity could be due to the fact that the free radical scavenging assay was a combined activity of a wide range of compounds, 21 absence of only flavonoids with particular hydroxyl position in the molecule 19 and finally radical scavenging activity is not only specific to presence of polyphenol groups or flavonoids.…”
Section: Discussionmentioning
confidence: 47%
“…2) and resulting colour change, proportional to the effect, can be quantified spectrophotometrically. Based on the DPPH free radical scavenging effectiveness, it has been established that numerous polyphenolic compounds of different classes are strong antioxidants (Okawa et al, 2001;Villaño et al, 2007;Vladimir-Knežević et al, 2011). Also frequently used colorimetric method is Trolox equivalent antioxidant capacity (TEAC) assay, which is based on scavenging of blue-green ABTS radical cation by antioxidants present in sample (Nenadis et al, 2004).…”
Section: Chemical-based Antioxidant Assaysmentioning
confidence: 99%